The Effects of Cation Ratios on Root Lamella Suberization in Rice (Oryza sativa L.) with Contrasting Salt Tolerance. (16th May 2012) - Momayezi, M. R.; Zaharah, A. R.; Hanafi, M. M.
Abstract : Rice is an important produced cereal in the world. We evaluated the effect of salt compositions including NaCl and Na2 SO4 on suberin lamellae as a major barrier to radial ion and water movements in two rice genotypes representing contrasting salt tolerance levels under salinity stress. Two rice genotypes, Fajr as salt tolerant and Khazar as salt sensitive, were transplanted in sand culture under glasshouse condition. Rice seedlings were treated with five salt compositions including NaCl, Na2 SO4, 1 : 1, 1 : 2, and 2 : 1 molar ratios for 40 days. It was proven that suberin lamellae in endodermis of root cell wall were thickened with Na2 SO4 treatment. The results demonstrated that the number of passage cells was higher in Fajr genotype than that in Khazar genotype under saline condition. Calcium concentration in root tissue decreased as the SO 4 2 - concentration in root media increased. It can be concluded that Fajr genotype is able to keep some passage cells open to maintain Ca 2+ uptake. The Ca 2+ /Na + ratio in shoot tissue can be also a reliable index for the early recognition of salt stress in these rice genotypes.